PERAN SERTA PERKUMPULAN PEMUDA NUSANTARA JAWA SUMATERA (PENJARA) DALAM PENCEGAHAN TERJADINYA TINDAK PIDANA KORUPSI STUDI KASUS DEWAN PIMPINAN PUSAT PERKUMPULAN PEMUDA NUSANTARA JAWA SUMATERA (PENJARA) - Nanda, Satria; Falahiyati, Nurhimmi; Sahbudi, Sahbudi (Jurnal Sosial Humaniora Sigli, 2024)
One of the most scrutinized crimes in Indonesia is corruption. Corruption in the private sector is as severe as in the public sector, especially when business activities are linked to public sectors such as taxation, banking, and public services. The Nusantara Jawa Sumatera Association, known as "PENJARA," is an organization dedicated to preventing corruption in the regions of Java and Sumatra. This organization comprises committed members focused on the integrity of the Indonesian nation. The role of PENJARA in development activities, including efforts to prevent and eradicate corruption, is crucial as a social check to enhance public welfare and establish a professional, corruption-free bureaucracy. This study addresses the government's role in optimizing the prevention and eradication of corruption in Indonesia and how the youth organization PENJARA contributes to these efforts. The study reveals that government efforts in combating corruption face significant challenges, including synchronizing legislation, improving human resources, and digitization. PENJARA plays a vital role by conducting outreach, discussions, and dialogues with the public and government to prevent corruption and limit the opportunities for corrupt activities.